Relación entre la producción agrícola y el producto bruto interno en la región Loreto, periodo 2010-2019 - Vásquez Flores, Carlos Luis (2022)
The Loreto region is the largest region in geographical terms of Peru, likewise, a large part of this territory is covered by a great diversity of flora and fauna in the department of Loreto, therefore, it would be expected that the agricultural industry is one of the most productive in the region. Given this expectation, the initiative of this research was born since it will seek to determine what type of relationship the production of the agricultural sector has with the gross domestic product (measured in real terms) of the Loreto region during the period of time 2010 - 2019, and verify if said relationship is significant or not. The results show that there is a positive relationship between the study variables since a value of the Pearson correlation coefficient is obtained in relative terms of 41.54%. In another instance, it is determined through the estimation of a linear regression econometric model that the relationship between agricultural production and GDP is not significant since a p-value was obtained corresponding to the estimator of the coefficient of the independent variable (agricultural production ) of 0.2325, which is greater than 0.05, taking into account that the level of significance used was 5%.